Dear mom and dad : a letter about family, memory, and the America we once knew - Davis, Patti (Liveright Publishing Corporation, a division of W.W. Norton & Company, 2024)
"A remarkably poignant writer for our troubled times, Patti Davis writes about love, loss, and the power of redemption in this poetic letter to her long-gone parents"--